2021
DOI: 10.1039/d1ra04843k
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly estimation of isosorbide dinitrate and hydralazine hydrochloride using Green Analytical Quality by Design-based UPLC Method

Abstract: Analysing isosorbide dinitrate and hydralazine by using an eco-friendly method is an initial stepping stone towards environmentally benign method development, and its combination with the AQbD makes it the method to use for ages without revalidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…GAPI [ 45 , 46 ] is another qualitative method, used to measure the greenness based upon the stages involved in an analytical method. GAPI focuses on two aspects: (I) sample preparation and (II) instrumentation assessment.…”
Section: Resultsmentioning
confidence: 99%
“…GAPI [ 45 , 46 ] is another qualitative method, used to measure the greenness based upon the stages involved in an analytical method. GAPI focuses on two aspects: (I) sample preparation and (II) instrumentation assessment.…”
Section: Resultsmentioning
confidence: 99%
“…A design of experiment-based robustness study was performed to determine the probability of risk or failure [29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The critical analytical attributes (CAAs) are selected from the finalized method conditions, which significantly impact the separation of components, and verified against respective critical quality attributes (CQAs).…”
Section: Design Of Experiments Studymentioning
confidence: 99%
“…The primary purpose was to identify the method's sustainability, although five evaluation tools employed diverse methodologies or processes to analyze the method's greenness. Regardless of their tactics, all of the methodologies indicated that this technique is environmentally benign and flexible to future green assessment without any problems [35].…”
Section: Agree With Metricsmentioning
confidence: 99%